Asymptotic tail behavior of a random sum with conditionally dependent subexponential summands. Issue 12 (18th June 2017) - Zhang, Yanfang; Cheng, Fengyang
ABSTRACT: In this paper, we obtain some results for the asymptotic behavior of the tail probability of a random sum S τ = ∑ τ k = 1 Xk, where the summands Xk, k = 1, 2, …, are conditionally dependent random variables with a common subexponential distribution F, and the random number τ is a non negative integer-valued random variable, independent of { Xk : k ⩾ 1}.